Guinea-Bissau - Public Expenditure Review Update : Enhancing Growth and Fiscal Adjustment Through Civil Service Reform - World Bank (World Bank, 2012)
Guinea-Bissau's large public sector wage bill poses a major threat to the country's macroeconomic stability: it hampers growth, limits the government's ability to service the domestic and external debt, and crowds out private investments. For this reason, the government decided in early 2006 to retrench more than 2,800 civil servants in a first phase, and about 1,600 military later. The objectives of this public expenditure review (PER) update are to: (i) review progress in macroeconomic and fiscal management since the previous PER; (ii) analyze the issue of compensation benefits in the context of the ongoing civil service reform; and (ii) update the debt sustainability analysis for Guinea-Bissau. Besides this introduction, the report includes three main chapters on macroeconomic management, improving the fiscal situation, and debt sustainability. The report also gives a final conclusion and discusses the way forward.